Considerações relevantes na seleção de dentes artificiais - Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP]; Moreno, Amália [UNESP]; Fajardo, Renato Salviato [UNESP]; Gennari Filho, Humberto [UNESP] (My University, 2011)
Nowadays the search for aesthetic in removable dentures is considered a success clinical factor. Besides, both the selection of artificial denture teeth and the characterization of dentures have been based on the facial harmony and cultural factors. But these factors change over time. Therefore, the present study aimed to discuss the selection of artificial denture teeth in relation to patient’s variables such as face shape, skin color, hair color, eye color, age and gender. Moreover, artificial denture teeth’ color, shape and size were presented.

Atualmente a busca pela estética em próteses removíveis é considerada um fator de sucesso clínico. Associada a isso, a seleção dos dentes artificiais e caracterização de próteses têm sido baseadas principalmente na harmonia facial e fatores culturais, que se modificam ao logo do tempo. Dessa forma, este trabalho objetivou discutir as formas de seleção dos dentes artificiais diante de variáveis como forma do rosto, cor da pele, cor do cabelo, cor dos olhos, além da cor, forma e tamanho dos dentes artificiais, sexo, idade, e estruturas anatômicas relevantes na composição estética das próteses removíveis.
Relevant considerations to select artificial denture teeth
Keywords: Tooth artificial; Aesthetic; Dental prosthesis; Dente artificial; Estética; Prótese dentária